Literature review on Chinese character design - Zhu, Hongyu; Alli, Hassan; Abidin, Sazrinee Zainal (Human Resources Management Academic Research Society (HRMARS), 2024)
With the advent of the information age, typeface design as an important element of visual communication by People's attention. Good typeface design can accurately express and convey information in daily life, at the same time, it can enhance the artistic sense and aesthetic value of typeface design, and promote the inheritance and development of traditional culture. At present, there are some problems in Chinese character design, such as the lack of visual aesthetics and how to achieve the innovation and development of Chinese character design while inheriting Chinese culture. By means of literature research, the development trend, background, existing research achievements and shortcomings of Chinese character design in different periods are discussed.The study found that with the rapid development of technology, the impact of globalization, new technology and the cultural value of Chinese characters, how to pass on the culture while continuing to do a good job of innovation and development has become a need to solve the task of the times.In the future research, we need to further explore how to promote the development of font design and improve the functional application of typography through scientific and technological means and innovative methods.